Caracterização biológica de extratos de prosópolis de diferentes regiões geográficas obtidos por Extração com Fluido Supercrítico e Extração Etanólica - Machado, Bruna Aparecida Souza (2015)
Propolis is a resinous material collected by bees from sprouts and barks of different vegetable source and the propolis has pharmacological and biological properties attributed to the presence of different classes of phenolic compounds. The supercritical fluid extraction (SFE) is an operation that explores the solvation power of fluids at temperature and pressure above its critical values, to extracting or separating components of a sample. This technology has been effective for obtaining extracts from natural matrices. The aim of the study was to define the best process conditions for obtaining Brazilian green propolis extracts (from Paraná) using the SFE. For that definition, the influence of different parameters was evaluated, such as S/F (solvent mass – CO2 – relative to solute mass – propolis), percentage of co-solvent (1 and 2% ethanol), temperature (40 to 50°C) and pressure (250, 350 and 400bar) using supercritical carbon dioxide (CO2). The Global Yield Isotherms (GYIs) were obtained through the evaluation of the yield, and the chemical composition of the extracts was also obtained in relation to the total phenolic compounds, flavonoids, antioxidant activity and 3,5-diprenil-4-hidroxicinamic (Artepillin C) and Acid 4-hidroxicinmic (p-coumaric acid). Furthermore, considering that the variations in the chemical composition, and consequently in the biological activity of propolis are associated with the type and geographical origin, samples of eight different propolis were evaluated, obtained by supercritical fluid extraction (SCO2 - 50°C, 350bar, 1% co-solvent and S/F 110) and ethanoic extraction (EtOH - 80% at 70°C). The evaluated samples were: red (Alagoas and Sergipe), green (Minas Gerais and Paraná) and brown (Paraná, Santa Catarina and Rio Grande do Sul). The samples were characterized referring to protein, lipids, ash, minerals (sodium, potassium, calcium and lithium), fiber, water activity and analyzed by scanning electron microscopy (SEM). The extracts were analyzed for their content of phenolic compounds, flavonoids, in vitro antioxidant activity (DPPH and ABTS), quantification of Artepillin C and p-coumaric acid by high-performance liquid chromatography (HPLC) and antimicrobial activity. The EtOH extracts were evaluated as the anti-proliferative activity against B16F10 cell lines (murine) as well. For the SFE application as an extraction method to obtain propolis extract (green propolis from Paraná), the best results were found at 350bar, 50°C, presence of 1% ethanol (co- solvent) and 110 S/F. Under these conditions, a content of 8.93±0.01 and 0.40±0.05g/100g Artepillin C and p-coumaric acid were identified, respectively, showing efficiency of the extraction process. Regarding to the comparative analysis of EtOH and SCO2 extracts of different samples, the red propolis from northeastern Brazil (Sergipe and Alagoas) showed the highest biological potential and the highest content of antioxidant compounds. The best results were presented for the extracts obtained from the conventional extraction (EtOH). It was found that despite the low yield of the process, the extracts obtained by SFE showed elevated levels of compounds of interest, as well as proving to be a viable process to obtain propolis extracts. The best results of antioxidant activity were presented by red and green propolis, thus demonstrating the biological potential of these samples. Finally, there is the composition and biological activity of Brazilian propolis varies significantly depending on the sample type, geographic region gathering and extraction conditions.